2012
DOI: 10.1111/j.1399-5618.2011.00969.x
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life in bipolar disorder

Abstract: HRQOL is significantly adversely affected in BD patients. Additionally, the presence of comorbid conditions highly prevalent in BD further decreases HRQOL for these patients. In spite of these factors, this review offers renewed hope as several treatment regimens correlate with higher post-intervention HRQOL scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(60 citation statements)
references
References 54 publications
4
49
0
7
Order By: Relevance
“…Por otra parte, se estableció que los pacientes bipolares obtienen puntajes significativamente menores que el grupo no clínico, tanto en el cuestionario SF-36v.2 como en el QoL.BD-CL (p < 0,001). Esta diferencia en la percepción de la calidad de vida es congruente con los resultados de estudios previos 4,12,17,18,19 . Es importante destacar que se obtuvo información referida a la sensibilidad y especificidad del instrumento, aspecto que no se había informado previamente.…”
Section: Discussionunclassified
“…Por otra parte, se estableció que los pacientes bipolares obtienen puntajes significativamente menores que el grupo no clínico, tanto en el cuestionario SF-36v.2 como en el QoL.BD-CL (p < 0,001). Esta diferencia en la percepción de la calidad de vida es congruente con los resultados de estudios previos 4,12,17,18,19 . Es importante destacar que se obtuvo información referida a la sensibilidad y especificidad del instrumento, aspecto que no se había informado previamente.…”
Section: Discussionunclassified
“…Next to a higher risk for cardiovascular diseases (CVD) (Prieto et al, 2014) and associated increased mortality rates (Fiedorowicz et al, 2014), patients with bipolar disorder are more likely to experience an impaired quality of life (IsHak et al, 2012). Relative to the extensive literature now available on many aspects of CVD in bipolar disorder (Swarz & Fagiolini, 2012;Smith et al, 2013;Vancampfort et al, 2013a), there is limited evidence available concerning the influence of increased medical co-morbidities on the functional limitations in daily living in patients with bipolar disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, when symptom reduction is obtained, it is expected to obtain improvement in psychosocial functioning. However, even with this improvement, patients do not achieve premorbid level of functioning (5). In our study, we found that second generation antipsychotics (SGA) in combination with mood stabilizers (MS) seem to affect psychosocial functioning negatively (28).…”
Section: Factors Affecting Quality Of Life and Functioning In Bipolarmentioning
confidence: 78%